2013
DOI: 10.4236/ojce.2013.33015
|View full text |Cite
|
Sign up to set email alerts
|

Using Multivariable Linear Regression Technique for Modeling Productivity Construction in Iraq

Abstract: Productivity is a very important element in the process of construction project management especially with regard to the estimation of the duration of the construction activities, this study aims at developing construction productivity estimating model for marble finishing works of floors using Multivariable Linear Regression technique (MLR). The model was developed based on 100 set of data collected in Iraq for different types of projects such as residential, commercial and educational projects. Which these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 24 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…There are some commonly used techniques to build a predictive model with high accuracy invented by several previous studies such as regression, learning curve and neural networks. Al-Zwainy et al. (2013) indicated that the average error is nearly 4.0% when using multivariable linear regression to model construction productivity.…”
Section: Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some commonly used techniques to build a predictive model with high accuracy invented by several previous studies such as regression, learning curve and neural networks. Al-Zwainy et al. (2013) indicated that the average error is nearly 4.0% when using multivariable linear regression to model construction productivity.…”
Section: Analysis Resultsmentioning
confidence: 99%
“…There are some commonly used techniques to build a predictive model with high accuracy invented by several previous studies such as regression, learning curve and neural networks. Al-Zwainy et al (2013) indicated that the average error is nearly 4.0% when using multivariable linear regression to model construction productivity. Khanh and Kim (2014) proved that the maximum absolute percentage error (MAPE) of a learning curve-based model is approximately 5.0% for predicting construction productivity for formwork, rebar and concrete activity in high-rise buildings.…”
Section: Validation Of the Accuracy Of Proposed Modelmentioning
confidence: 99%
“…The author used the same procedure that was followed by Al-Zwainy et al [3] for exploring the comprehensive survey. The comprehensive survey was collected via previous studies from local and international journal papers, research reports, conference proceedings, theses, dissertations, and Internet publications.…”
Section: Study Methodologymentioning
confidence: 99%
“…Regression analyses are among the most widely used models for construction labor productivity prediction. One of the most frequently used among these analyses is linear regression models (Al-Zwainy et al, 2013;Ghodrati et al, 2018;Gurmu and Aibinu, 2017;Hai and Van Tam, 2019). More accurate predictions can be made by reducing variance and bias in linear regression algorithms.…”
Section: Ecam 313mentioning
confidence: 99%
“…Labor productivity plays a fundamental role in building production (Golnaraghi et al, 2020a), because the share of labor productivity is great at every critical stage of the construction process, including cost, time and quality (Al-Zwainy et al, 2013;Mlybari, 2020;Momade et al, 2020). One of the most important reasons for this is that many factors impact labor productivity (Mlybari, 2020).…”
Section: Introductionmentioning
confidence: 99%